A Randomized Trial Among Compression Plus Nonsteroidal Antiinflammatory Drugs, Aspiration, and Aspiration With Steroid Injection for Nonseptic Olecranon Bursitis. Issue 3 (March 2016) - Kim, Joon Yub; Chung, Seok Won; Kim, Joo Hak; Jung, Jae Hong; Sung, Gwang Young; Oh, Kyung‐Soo; Lee, Jong Soo
Abstract: Background: Olecranon bursitis might be a minor problem in the outpatient clinic but relatively be common to occur. However, there are few well‐designed studies comparing approaches to treatment. Questions/purposes: (1) Which treatment (compression bandaging with nonsteroidal antiinflammatory drugs [NSAIDs], aspiration, or aspiration with steroid injections) is associated with the highest likelihood of resolution of nonseptic olecranon bursitis? (2) Which treatment is associated with earliest resolution of symptoms? (3) What factors are associated with treatment failure by 4 weeks? Methods: We enrolled 133 patients from two centers; after applying prespecified exclusions (septic bursitis or concomitant inflammatory arthritis, intraarticular elbow pathology, recent aspiration or steroid injection done elsewhere, and refusal to participate), 90 patients were randomly allocated to receive compression bandaging with NSAIDs (C), aspiration (A), or aspiration with steroid injection (AS) groups (30 patients in each). The groups were similar at baseline in terms of age and gender. Seven patients (four from Group A and three from Group AS) were lost to followup. All patients were followed up weekly for 4 weeks, and the same treatment procedure was repeated if the bursitis recurred with any substantial fluid collection. At 4 weeks, the state of resolution and pain visual analog scale (VAS) were evaluated. Failed resolution was defined as presence of persistent olecranon bursal fluid collection at Week 4 after the initiation of the treatment; on the contrary, if bursal fluid collection was clinically reduced or completely disappeared by the end of Week 4, the treatment was considered successful. We compared the proportion of resolution by Week 4 and the median times to resolution among the treatment groups. In addition, we evaluated whether the resolution affected pain VAS and what factors were associated with the resolution. Results: There were no differences in the proportion of patients whose bursitis resolved by Week 4 among the three treatment groups (Group C: 25 of 30 [83%], relative risk of resolution failure: 0.68 [95% confidence interval CI, 0.27‐1.72], p = 0.580; Group A: 17 of 26 [65%], relative risk of resolution failure: 2.19 [95% CI, 0.98‐4.87], p = 0.083; Group AS: 23 of 27 [85%], relative risk of resolution failure: 0.59 [95% CI, 0.22‐1.63], p = 0.398) (p = 0.073). Steroid injection after aspiration (Group AS) was associated with the earliest resolution (2.3 weeks [range, 1‐4 weeks]) when compared with aspiration alone (Group A; 3.1 weeks [range, 2‐4 weeks]) and compression bandaging with NSAIDs (Group C; 3.2 weeks [range, 2‐4 weeks]), p = 0.015). Longer duration of symptoms before treatment was the only factor associated with treatment failure by 4 weeks (failed resolution: 6 weeks [range, 2‐9 weeks]; successful resolution: 4 weeks [range, 0.4‐6 weeks]; p = 0.008). Conclusions: With the numbers available, there were no differences in efficacy when compression bandaging with NSAIDs, aspiration, and aspiration with steroid injection were compared. However, we were powered only to detect a 30% difference, meaning that if there were a smaller difference in efficacy among the groups, we might not have detected it in a study of this size. Our data can be used as pilot data to power future prospective (and likely multicenter) trials. Because olecranon bursitis can recur, and because treatments like aspiration and aspiration with steroid injection can cause complications, unless future trials demonstrate clear efficacy advantages of aspiration and/or injection both at short and longer terms, we suggest that compression bandaging and a short course of NSAIDs may offer the most appropriate balance of safety and efficacy. Level of Evidence: Level II, therapeutic study.